MR T2* Map to Predict Worsening Hypertension Control: A Preliminary Study - Chun-Hung Liu; Jeon-Hor Chen; Antonio Carlos Westphalen; Chun-Ming Chen; Chih-Ping Chang; Wei-Ching Lin (Life)
Blood pressure measurement is important in monitoring hypertension. However, blood pressure does not provide much information about renal condition in treated hypertension. This study aimed to evaluate renal oxygenation in hypertensive patients using T2* mapping. Subgroup analysis explored whether R2* values can guide adjustments in antihypertensive treatment. A total of 140 consecutive subjects were recruited: 87 hypertensive subjects and 53 normotensive subjects. Hypertensive subjects were classified into non-medication (non-med), angiotensin II receptor blocker (ARB), and non-ARB-treated groups. Each group was divided into good and poor control subgroups based on blood pressure at enrollment. T2* mapping was utilized to assess renal cortical and medullary R2* values. After a 2-year follow-up, subjects were categorized into stable and unstable based on the need for treatment modifications. The unstable subgroup had higher medullary R2* values than the stable subgroup in all followed patients (p < 0.05). Additionally, the unstable merged non-med with ARB subgroup had higher medullary R2* values overall (p < 0.05) and within the good control subgroup (p < 0.05). Patients with stable hypertension, especially those with good control managed through lifestyle modifications or ARBs, exhibited lower renal medullary R2* values, suggesting higher renal oxygenation.